Overcoming opioid addiction : the authoritative medical guide for patients, families, doctors, and therapists - Bisaga, Adam; Chernyaev, Karen, 1961-; McLellan, A. Thomas (Andrew Thomas), 1949- (The Experiment, 2018)
Every day, over 100 Americans die from opioid abuse. Bisaga and Chernyaev provide a comprehensive medical guide for opioid use disorder (OUD) sufferers, their loved ones, clinicians, and other professionals. He explains why treating OUD is unlike treating other forms of drug dependency, examines the science of the addiction, and discusses the different stages and effective methods of treatment, as well as behavioral therapies.